Retrospective evaluation of the applications within the scope of probation implementation: the data of 2018 - Eğilmez, Oğuzhan Bekir; Örüm, Mehmet Hamdi; Kara, Mahmut Zabit (Journal of Dependence, 2019)
Objective: The leading centers in the treatment of substance use disorder (SUD) in Turkey are the Alcohol-Drug Addiction Research Treatment and Training Centers (AMATEM). In this study, we aimed to examine 2018 data of the single AMATEM outpatients in Adıyaman. Method: The study was conducted as a retrospective study of AMATEM applications within 2018. Information such as gender, age and substance use characteristics of the applications were obtained from the patient recording system. Results: A total of 401 applications were reached. The mean age was 25.75±6.90 years. The mean age was significantly higher in patients with alcohol use disorder than in the other diagnoses. 84.8% of the patients were diagnosed with opiate use disorder (OUD). The repeated applications were significantly higher in OUD than in other applicants. The rate of prescribing of buprenorphine+naloxane in OUD was 77.6%. Buprenorphine, buprenorphine+opiate and opiate positivity was higher than other parameters in urine toxic screening. Conclusion: This study is important in terms of revealing that opiate use is a serious problem in Adıyaman, Turkey.